PERTANGGUNGJAWABAN PIDANA PELAKU PEMALSUAN SURAT DAN PENCURIAN KONTENER DENGAN PEMBERATAN DI JAKARTA UTARA: Criminal Accountability for Forger of Ketter and Container Theft With Weight in North Jakarta - Prasetyo, Pandya Dimas; Multiwijaya, Vientje Ratna (Faculty of Law, Universitas Trisakti, 2024)
The criminal responsibility of the perpetrators of the crime of theft which began with falsifying a letter resulted in a loss of Rp. 40,000,000.00 to the victim, but in fact the judge's decision was not satisfactory because it only used Article 363 paragraph 1 4 of the Criminal Code as illustrated in the Decision of the Central Jakarta District Court No. . 113/Pid.B/2022/PN Jkt Utr. The main issue raised is How is the criminal responsibility of the perpetrator, is it appropriate based on Article 363 paragraph 1 4 of the Criminal Code? and Is the perpetrator's actions included in the combination of criminal acts? This study uses a Normative Juridical research method which is Analytical Descriptive in nature by using Secondary Data obtained from literature studies which are then processed qualitatively. Deductive conclusions are in the form of (1) The perpetrator's liability is not appropriate if only using Article 363 paragraph 1 to 4 singly because it also fulfills the formulation of Article 263 paragraph 1 of the Criminal Code and the perpetrator's actions are included in a combination of criminal acts, namely Continuing Actions resulting in inappropriate perpetrator accountability if only subject to Article 363 paragraph 1 to - 4, but he should also be subject to Article 263 paragraph 1 of the Criminal Code concerning Forgery of Letters, besides that his actions are included in a combination of criminal acts, namely Vorgezette Handelling with sharpened punishment in order to achieve contemporary criminal purposes and goals 3R +1D.